Low cost fabrication of micromixer and microchamber for microfluidic lab-on-chip - Uda, Hashim, Prof. Dr. (Institute of Electrical and Electronic Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/